Strategi Komunikasi Pemerintah Kabupaten Blora Menuju Smart City - Nisrina Meitibellina; Puji Hariyanti (Jurnal Komunikasi, 2020)
This study discusses the communication strategy carried out by Blora Regency Government in the program of the Ministry of Communication and Information, namely Gerakan Menuju Smart City 2018. There are two statements in this research is how the communication strategy carried out by Blora Regency Government towards smart city and the factors that are driving and inhibiting it.The results obtained from Gerakan Menuju 100 Smart City program in Blora Regency are based on a predetermined policy in the form of the RPJMD and the Decree of the Regent. Then proceed with analyzing problems related to city problems to create the concept of smart city that requires 3 elements namely structure, infrastructure and superstructure. The targets for this program are all OPD’s and the Blora community. The use of various media for socialization which then its implementation refers to the 2018 smart city master plan and ends with monitoring and evaluation every 2 times a year. There are 6 dimensions of the concept of smart city along with several activities in it that are used in Blora Regency, namely smart governance, smart branding, smart economy, smart living, smart society and smart environment.\Keywords: communication strategy, gerakan menuju 100 smart city, Blora Regency